Tinjauan Yuridis Mengenai Harta Peninggalan dari Pewaris Mualaf Terhadap Saudara Kandung Non-Muslim dalam Perspektif Hukum Waris Islam di Indonesia - Nabilla Shafa Azzahra; Renny Supriyatni; Sridewei Anggraeni Wiyono (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2024)
The purpose of this study is to analyse the juridical review of the inheritance of a convert heir to a non-moslem sibling in the perspective of Islamic inheritance law in Indonesia. This research was conducted using descriptive analytical normative legal research, using secondary data obtained from literature studies as the main data and using primary data, namely related legislation as supporting data, research data collection techniques using library research, and data analysis using qualitative juridical data analysis. Based on the results of the study, it shows that the judge's legal considerations when examined based on Islamic law, the siblings are already Catholic. A person who is of a different religion from the heir is cut off from the right to inherit because it is hindered by law, this is as the hadith of the Prophet Muhammad SAW and Article 171 letter c KHI. Article 172 KHI also states that a person's Islamic faith, apart from being seen from the Identity Card, can also be seen from confession or practice or testimony. The settlement of inheritance of different religions can be found through the Ijtihad method.